Perceptions of Florida-Friendly Landscapes: Linking Visual Quality and Environmental Health through Landscape Codes: ENH1258/EP519, 4/2015 - Hansen, Gail; Warner, Laura; Monaghan, Paul; Ott, Emily; Fogarty, Tim; Momol, Esen (EDIS, 2015)
The Florida-Friendly Landscaping™ program (FFL) was established in 1994 to promote environmentally friendly landscapes that conserve water and protect the environment. The primary goal of the program is to encourage the adoption of environmentally friendly landscape behaviors, including using the right plant in the right place. Early efforts to promote Florida-Friendly landscapes emphasized the use of drought-tolerant plants, which created a common misconception that an FFL yard is a "natural-looking" xeriscape with an unkempt appearance. The negative association with a visually unappealing landscape has hampered the promotion of FFL yards and the adoption by homeowner associations (HOAs) as the landscape to promote in regulations and codes.